Analisis Pengaruh Citra Merek, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk Kosmetik Wardah - Muryati Muryati; Ade Jermawinsyah Zebua (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study is to determine the effect of the variable brand image, price and product quality partially and simultaneously on purchasing decisions for wardah lipstick products, in addition to knowing the most dominant variables in making wardah lipstick purchasing decisions. This research is a comparative causal research with a quantitative approach. . The variables in this study are brand image, price, product quality and purchasing decisions as the dependent variable. The population in the study were all sixth semester students at the Graha Karya Muara Bulian School of Economics, which amounted to 40 respondents. The results of the study indicate that the influence of brand image, price and product quality partially from each variable has a positive and significant effect on purchasing decisions while simultaneously all variables X1, X2 and X3 have a positive and significant effect on purchasing decisions Lipstick wardah in sixth semester female students. Graha Karya Muara Bulian School of Economics. From the analysis results indicate that the Adjusted R Square value of 0.623 means that the variable brand image, price and product quality 62.3% affect the purchasing decision of Wardah lipstick and 37.7% is influenced by other variables not examined in this study.